EFFECT OF STRAIN AND TERPERATURE ON SOME SEMENAL CHACTERISTICS OF LOCAL TURKEY MALRS - Th. Taha, N.; W. AL Doori, T.; J. Howaizi, D.; B.Al-Deen , S.; Y. Taha., S. (The Iraqi Journal of Veterinary Medicine, 1989)
This study was conducted at the turkey farm of the College of Agriculture, Salahaddin University, by using (7) black and (10) red local turkey males to study the effect of strain and environmental temperature on some semen characteristics (Semen volume, colour, pH, Individual and mass sperm motility, live and abmormal sperm percentage, and aperm concentration in cu. ml. and in ejaculate, and to study the relation between paire of characters under study. Analysis of voriance showed that strain had a signifiant effect (p<0.05) only on mass sperm motility and sperm concentration in cu ml traits. Tnviromental temperature showed a significant effect (p<0.01) on all traits accept for pH and live sperm percentage traits which had no significnt effect. Interation between strain and environmental temperature showed asignificant effect (p<0.05) on Indvidual sperm motility, abnormal sperm percentage and sperm concentation in cu. ml. traits. correlation Coefficients between pairs of traits were negative and significant (p<0.01, p<0.05) in most traits, accept those of percent abnormal sperms and pH traits which showed a negative, significant and not significant correlation coefficient, with most traits in study.